(untitled) (Research, Society and Development, 2020)
The objective of this study was to analyze some health indicators in order to understand the current situation of Covid-19 in South America and to contribute to the strengthening of strategies to face this pandemic in the continent. This is a descriptive study with a brief analysis of epidemiological indicators based on data updated daily, obtained from the website https://www.worldometers.info/coronavirus/ and compared with the relevant literature using primarily original studies. Despite the growth in testing rates among South America countries, the population coverage for infection detection testes still low. Thus, the actual proportion of the infected population is not known, and as a consequence, the planning of combat actions becomes more difficult. Investing in tests to detect infection and maintaining sanitary measures seems to be currently the most appropriate strategies for controlling the disease, while effective drugs for the treatment of disease and vaccines for prevention new cases are not available.